The Importance of Building Design and Its Contribution to Human Health - Alif Khusaini; Mohammad Arziz Raka Pradana; Dandi Kusmayandi (Universitas Komputer Indonesia, 2022)
The purpose of this research is to find out how important it is for a building that has a healthy building approach or concept that will have a positive impact on the users of the building itself. To support the research, we use the method of collecting data from several journals found related to the research title. The results of this study indicate that every design of a building must pay attention to the element of thermal comfort from each room, the concept of healing environment, pay attention to the use of materials, and must also apply the concept of sustainable architecture. In this study, things that must be considered are what the concept of thermal comfort is good for the health of the building users themselves, the concept of healing environment, the use of materials, and also the concept of sustainable architecture. It can be concluded that the building is said to be healthy if all the discussion criteria can be implemented properly. Users of the building itself, of course, not only feel the comfort of the building that is used, but can indirectly have a positive impact on the health of the users themselves, and can also survive in a fairly long period of time.